Data from the Mixed Methods Project PICE (Parental Investment in Children’s Education) - Marieke Heers; Sandra Hupka-Brunner; Andrés Gomensoro; Chantal Kamm (Journal of Open Psychology Data, 2023)
The Parental Investment in Children’s Education (PICE) study focuses on Switzerland and investigates parental strategies, resources, and aspirations and how they shape their children’s educational pathways. It contrasts families with a migration background to those without. PICE is a mixed-methods add-on-study of TREE (Transitions from Education to Employment). Within PICE one interview with young adults (N = 73, around age 20) and two interviews with one of their parents (N = 50) were conducted. The data are available for scientific analyses via SWISSUbase. They have reuse potential for analyses on parental investments, migration biographies as well as for methodological research on mixed methods.